Diversity and women in finance: Challenges and future perspectives - Girardone, Claudia; Kokas, Sotirios; Wood, Geoffrey (Journal of Corporate Finance, 2021)
This paper explores the main forces impacting diversity and the role of women at senior management and board level in finance. In addition, it offers a synopsis of selected research examining the board composition, corporate social responsibility and external corporate governance. We focus mainly on empirical papers that employ quasi-natural experiments and textual analysis to confirm the interdisciplinary nature of diversity. Further, we identify priorities for future research that can advance our understanding on this research area, and the broader field of financial studies, encompassing the growing interest in the boundaries between the economic, the psychological and the social.